Preparation and Evaluation of Diclofenac Sodium Niosomes Using Round Bottom Flask Method - Bhattacharya, Sankha (Asian Journal of Pharmaceutics (AJP), 2020)
Aim: The main objective of this study is to prepare and evaluate niosomes as a carrier for diclofenac sodium. Niosomes are bilayer microparticles formed by self-association of non-ionic surfactant and cholesterol after hydration in the aqueous phase. Materials and Methods: Niosomes of SPAN-60 and cholesterol were prepared in three batches (A, B, and C) with different ratio (5:5, 6:4, and 7:3) using a round bottom flask method. Prepared niosomes were evaluated for entrapment efficiency, particle size analysis, and morphology and in vitro drug release study. Results and Discussion: The entrapment efficiency of all three formulations was found to be 91.43%, 92.53%, and 92.33%, respectively. All formulations were observed under motic microscope and particles were assumed to be spherical in shape. The average particle size of all the three batches was analyzed by Zetasizer (Delsa C Particle Analyzer), and it was found that the batch C produced the best nano-sized formulation with an average particle diameter of 311.6 nm. In vitro release study was done using a dialysis bag and after 300 min of studies, batch C (7:3), which was found to have 68.6 Â± 1.4% cumulative drug release, which indicates controlled and steady drug release profiling of the formulation. Conclusion: After comparing all three batches of evaluation results on the basis of drug entrapment, particle size analysis, morphology, and in vitro drug release study, Batch C (7:3) formulation was considered as the best formulation.